Robust bandwidth allocation in wireless mesh network - Thuc, Tran Kien (2013)
Bandwidth allocation is important for a mesh network to meet quality of service (QoS) requirements of the users. This bandwidth allocation has to ensure that the maximum throughput is achieved. However, this problem becomes more challenging when the information about a network (e.g., channel quality and hence link capacity) is not accurately known, especially, in a real system whose parameters are uncertain. Therefore, in this paper, we apply the robust optimization technique to develop a model that can tolerate the uncertainty of the system parameters. First, we formulate the bandwidth allocation problem as a constrained optimization problem and its robust counterpart is obtained. Then, we suggest an approach to choose the suitable system parameters so that with a certain high probability, the feasibility of the solution from optimization formulation is ensured for all meaningful realizations of the system parameters. Moreover, we introduce the reduced conservativeness approach for the bandwidth allocation. In this approach, the tradeoff between throughput and robustness to the uncertainty of a system parameter is explored. Specifically, the decrease in throughput will be minimized given the target robustness.